2021
DOI: 10.1007/s11356-021-14206-9
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of GO/MIL-101(Fe,Cu) composite and its adsorption mechanisms for phosphate in aqueous solution

Abstract: In this study, , Cu), and Graphene Oxide (GO) /MIL-101(Fe,Cu) were synthesized to compose a novel sorbent. The adsorption properties of these three MOFs-based composites were compared toward the removal of phosphate. Furthermore, the influencing factors including reaction time, pH, temperature and initial concentration on the adsorption capacity of phosphate on these materials as well as the reusability of the material were discussed. The structure of fabricated materials and the removal mechanism of phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…PXRD can be used to accurately and efficiently detect the crystallinity of samples, and the structural characteristics of the samples can be determined by comparing the PXRD patterns of products ( Figure 2 ) [ 41 , 42 , 43 ]. Here, the synthesized products were investigated with PXRD by varying the addition ratio of FeCl 3 ∙6H 2 O and silver nitrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PXRD can be used to accurately and efficiently detect the crystallinity of samples, and the structural characteristics of the samples can be determined by comparing the PXRD patterns of products ( Figure 2 ) [ 41 , 42 , 43 ]. Here, the synthesized products were investigated with PXRD by varying the addition ratio of FeCl 3 ∙6H 2 O and silver nitrate.…”
Section: Resultsmentioning
confidence: 99%
“…In the FTIR spectra of MIL-101(Fe)@Ag ( Figure 3 ), the C–H bond of the benzene ring remained at 751 cm −1 . The characteristic peaks at 1396 and 1583 cm −1 are the symmetric and asymmetric vibrations of the carboxyl group (–COO–), while the characteristic peak at 1680 cm −1 is associated with the presence of a C=O bond in the free carboxyl group, indicating the presence of a continuous dicarboxyl linkage [ 41 , 42 , 43 , 44 ]. This showed that the peaks of MIL-101(Fe) were still present in the FTIR spectrum of MIL-101(Fe) loaded with silver ions.…”
Section: Resultsmentioning
confidence: 99%
“…The FT-IR spectrum shows a strong peak at 1393.1589 cm −1 corresponding to the symmetrical and asymmetrical oscillations of the carboxylic group in the BDC coordinated with cobalt and iron ions. The absorption peaks at 527 and 751 cm −1 come from the bond formed by Fe 3+ , the carboxylic acid functional group (Fe-O), and characterize the C-H bond vibration of the benzene ring [25]. Basically, the characteristic peaks of CoFe-MOF are similar to those of Fe-MOF, with only some displacement and size of the peak of 662 cm −1 , which may be caused by the carboxyl group in terephthalic acid and Co 2+ [26].…”
Section: Characterization Of Materialsmentioning
confidence: 99%
“…Table 1 shows that the BET surface area of Fe-MOF of 32.8 m 2 /g increases to 280.9 m 2 /g when changing the center of the second metal in the lattice with a molar ratio of 0.3 Co:Fe. At the same time, the pore diameter and pore volume also change, creating suitable conditions for rapid diffusion of the adsorbed substances to the adsorption centers of the adsorbent, thereby increasing the adsorption capacity [25]. The specific surface area of the material is also affected by the change in the material morphology in the presence of Co 2+ ions; the crystal morphology changes from axial rotation to octahedral with two pointed ends, resulting in a larger specific surface area [27].…”
Section: Characterization Of Materialsmentioning
confidence: 99%
“…Simultaneously, the shape of metal ions determined the structure of MOFs after synthesis. With their porous structure, large surface area, stability, and high functional group activity, MOFs are promising candidates for various applications such as gas storage, catalysis, adsorption, drug delivery, and sensing [6][7][8][9]. Therefore, MOFs are expected to become promising materials for many fields in the future.…”
Section: Introductionmentioning
confidence: 99%